Factors Related to the Incidence of Ischemic Stroke in the Elderly - Frisma Mulya Ramdani; Hendra Kusumajaya; Arjuna Arjuna (Genius Journal, 2027)
Introduction : World Health Organization (WHO) data for 2022 states that there are 12,224,551 new cases each year. The prevalence of stroke in Indonesia in 2023 is 23.1 million people (8.3%) of a population of 277.5 million. Data from Bakti Timah Hospital, Pangkalpinang, states that there were 318 cases of stroke in 2024. Objective: The purpose of this study was to determine the factors associated with the incidence of ischemic stroke in the elderly at Bakti Timah Hospital, Pangkalpinang, in 2025 Method : The design in this study used a cross-sectional with independent variables (history of disease, diet and family support) and dependent variables (ischemic stroke in the elderly). The population size in this study was 318 people and a sample of 83 people, the calculation used simple random sampling. The research time was from 16 to June 2025 Result: The results of the study obtained a p-value of the knowledge variable 0.000 <0.05, diet 0.000 <0.05 and physical activity 0.000 <0.05. This shows that there is a significant relationship between medical history, diet and family support on the incidence of ischemic stroke in the elderly at Bakti Timah Hospital Pangkalpinang in 2025 Conclusion: Suggestions in this study are expected to be used as evaluation material that it is important to maintain a healthy diet, support and encouragement of motivation from the family so that the elderly are enthusiastic and motivated in dealing with their illness. This should be a greater concern for health institutions, especially in designing work programs with a wider reach, such as providing health education and counseling to the community